Water reporting in mining: Are corporates losing sight of stakeholder interests?. (15th April 2022) - Gilsbach, Lucas; Schütte, Philip; Franken, Gudrun
Abstract: The mining industry provides the raw materials needed for economic and social development. At the same time, it is a large user and, occasionally, polluter of shared water resources that form the foundation of healthy ecosystems and a dignified human life. Realizing a sustainable water use in mining operations requires meaningful information on mine site-water interactions that allows stakeholders to build opinions, make sustainability-oriented decisions on procurement, permitting or investment, and hold companies accountable for their water-related activities. The objective of this study is to evaluate the relevance and priorities of current corporate water disclosure in mining against the backdrop of stakeholder information requirements. Combining a content analysis of corporate water reporting of the world's ten largest mining companies and the results of a stakeholder perception survey reveals that disclosed information on tailings management as well as water-related regulations and compliance issues are well suited to satisfy stakeholder interests. In contrast, significant priority misalignment exists for many other disclosure aspects governing the interactions of mining and water resources, especially with respect to information on corporate water strategies, mine site-level management plans and water balances. Proposed reasons for this disparity include the use of standardized water reporting templates and a unilaterally focused reporting practice. However, the evaluation also reveals varying, partly opposing stakeholder perceptions implying that a water reporting practice satisfying all legitimate interests is hardly achievable. Based on these findings, we recommend increased flexibility to individualize mine site-level water reporting, expanding disclosed information on water strategies and management plans, as well as tailoring of reporting to a specific target audience in order to better align information in corporate water disclosures to stakeholder interests. Highlights: Corporate water disclosure does not match stakeholder interests. Stakeholders rate tailings, water strategies and management plans as most relevant. Corporates prioritize tailings, input/output and stakeholder engagement activities. Stakeholder's water risk perception is determined by the personal background. Diversity of stakeholder interests require a targeted and individualized reporting.